Le silenti logiche dello spirito (Materiali di Estetica. Terza serie, 2019)
This article reflects on an ambivalence in our relationship with the Word of God. On the one hand, it seems present and active, for a civilization that has put at its center the linguistic manifestation of the divine. On the other hand, the evidence that God is silent, and therefore silence must be regarded as the center of this problematic theophany. Our civilization seems to oscillate between the possibility that the logos is the absolute manifestation of the divine, and the possibility that the logos must be transcended to draw on a more subtler language. In the era of “epilogy”, which is the proper name for the decline of a civilization founded on the logos, it is perhaps given to music the task of transmitting the Meaning.